Analysis of Business Strategies in Dealing with Various Threats and In-Creasing Income at The Indonesian Classification Bureau of Tanjung Priok Main Branch - Muhammad Ichsan; Retno Kusumastuti (Yayasan Riset dan Pengembangan Intelektual, 2023)
PT. BKI does not only rely on classification services but also originates from its commercial business which covers a wide variety of sectors and can grow rapidly. The phenomenon that occurs where the commercial segment is still under the classification segment even though it has many service groups is the result because PT. BKI has so far only focused on the classification service business, where the non-classification (com-mercial) service business has not been touched on in depth in its strategic plan. This research is a quantita-tive descriptive study using a qualitative approach, namely a study that describes the condition of the object under study in the form of direct observation, conducting Focus Group Discussions (FGD) and surveys us-ing questionnaires. The data analysis method used in this study is an analysis using the IFE matrix, EFE matrix and SWOT matrix to find out the next alternative strategy. This position is achieved due to the pres-ence of great non-classification power. The following is a business strategy formed from internal and exter-nal factors: 1) Development of Human Resources through research and development activities; 2) Always make Cooperation MoUs with external partners in several cities; 3) Optimizing uniqueness in order to be able to compete with foreign companies; 4) Improving Marketing using new technological approaches; 5) Business expansion through Company Holding; 6) Synergy with subsidiaries and other SOEs in carrying out business strategies; 7) At a minimum apply the use of the same technology and management system as out-side companies.